From Belém to Marvila: The transfer of the Gas Plant and changes in the production process (1887-1957) - Matos, Ana Cardoso de (2018)
This article analyses the negotiations for the transfer of the Belém gas plant to the eastern part of the city of Lisbon: the construction of the Matinha gas plant ant the organization of this production process; and the evolution of gas consumption in Lisbon in the period between 1889 - when a new gas company appeared in Lisbon – and 1957, at which time the operation of the Matinha gas plant was taken up by a new company, marking the end of gas production from coal.